PEMBELAJARAN BERJARAK SEBAGAI KEJADIAN LITERASI: STUDI TENTANG PROGRAM VIRTUAL SHARING DI RUANG BELAJAR AQIL - Setiawan, Ari; Ramadhani, Iqbal; Ariwiguna, Wily (Journal of Documentation and Information Science, 2019)
The learning process changes from traditional becomes distance learning through the use of ICT. The learning process is part of knowledge management, both in individuals, groups and organizations. Ruang Belajar Aqil is a learning space for youth to learn from expertise dan practitioner in certain fields through Virtual Sharing activities. This research was conducted to find out information about distance learning as literacy event in RBA. Researchers used a qualitative approach to realize the concepts in this study. Researchers planned the result of this research can be used as program evaluation (Neuman, 2006), especially in the context of learning and learning for all parties involved.